Pajak Karbon, Green Bonds, dan Laporan Keberlanjutan untuk Mendukung Sustainability Development Goals 2030: Tinjauan Literatur Sistematis - Valentina Tumanggor, Dian (Magister Ilmu Akuntansi Universitas Jambi, 2024)
Global climate change has caused significant economic losses for various countries, including Indonesia, with estimated damages reaching IDR 544 trillion during 2020-2024. To address these challenges, sustainable fiscal policies and financial instruments such as carbon taxes, green bonds, and sustainability reporting play a crucial role in supporting the achievement of the 2030 Sustainable Development Goals (SDGs). However, despite the issuance of relevant regulations by the government, the implementation of these instruments remains suboptimal. This study employs the Systematic Literature Review (SLR) method by identifying relevant literature from 2020 to 2024 to explore the role of these instruments in achieving sustainable development. The literature review includes scientific articles employing various research methods and is aligned with the context and scope of this study. These articles were sourced from international journals relevant to the study's objectives. This study employs the Systematic Literature Review (SLR) method by identifying relevant literature from 2020 to 2024 to explore the role of these instruments in achieving sustainable development. The literature review includes scientific articles employing various research methods and is aligned with the context and scope of this study. These articles were sourced from international journals relevant to the study's objectives.